Recent Researchеs in the Field of Slavic Gospel. Some Critical Reflections (1999–2016) - Garzaniti, Marcello (Studia Ceranea, 2016)
In the last fifteen years, research on the Slavic Gospel manuscript tradition have reached new and important achievements especially with the spread of computer technology and digitization process. Taking into account progress in the study of the Greek manuscript tradition, the author explains some basic guidelines: the textual structure of the Gospel book, the Menologion pericopes, the Gospel book ornamentation, the new editions. At the end the main essays on individual manuscripts or on particular issues are introduced. The Slavic Gospel, therefore, is still a key issue of Slavic studies in the field of Slavic paleography, textual criticism, and linguistic analysis.